1925 Ind. Acts 496-97, § 7 - (:unkn) unknown (My University, 1925)
Created qualifications for receiving a concealed carry license, including bona fide residence or place of business in Indiana, or the United States with a permit from another state. Permits shall last one year and cost one dollar.
Keywords: CARRY - CONCEALED